Bisphenol A exposure disrupts the development of the locus coeruleus‐noradrenergic system in mice. Issue 6 (2nd July 2014) - Tando, So; Itoh, Kyoko; Yaoi, Takeshi; Ogi, Hiroshi; Goto, Shoko; Mori, Miyuki; Fushiki, Shinji
<x xml:space="preserve">Abstract</x> It has been reported that bisphenol A (BPA), a widespread xenoestrogen employed in the production of polycarbonate plastics, affects brain development in both humans and rodents. In the present study employing mice, we examined the effects of exposure to BPA (500 μg/kg/day) during fetal and lactational periods on the development of the locus coeruleus (LC) at the age of embryonic day 18 (E18), postnatal 3 weeks (P3W), P8W and P16W. The number of tyrosine hydroxylase‐immunoreactive cells (TH‐IR cells) in females exposed to BPA was decreased, compared with the control females at P3W. At P8W, the number of TH‐IR cells in females exposed to BPA was significantly decreased, compared with the control females, whereas the number of TH‐IR cells in males exposed to BPA was significantly increased, compared with the control males, which resulted in reversed transient sexual differences in the numbers of TH‐IR cells observed in the controls at P8W. However, no significant changes were demonstrated at E18 or P16W. Next, we examined the density of the fibers containing norepinephrine transporter (NET) in the anterior cingulate cortex (ACC) and prefrontal cortex, at P3W, P8W and P16W, because NET would be beneficial in identifying the targets of the LC noradrenergic neurons. There were no significant differences shown in the density of the NET‐positive fibers, between the control and the groups exposed to BPA. These results suggested that BPA might disrupt the development of physiological sexual differences in the LC‐noradrenergic system in mice, although further studies are necessary to clarify the underlying mechanisms.